Teachers' enactments of character education: A case study from Indonesia - Maulana, Mochammad Ircham (Jurnal Pendidikan Karakter, 2022)
The Indonesian national curriculum and educational policies mandate the integration of character education into every classroom learning activities in schools. This qualitative case study aims to investigate Indonesian subject teachers' agency to enact character education, including how they plan, assess, and execute it, in their teaching practices. In addition, it also explores the ways they select the character traits as well as the challenges they encountered in character education. The data include in-depth semi-structured interviews with three experienced Indonesian senior high school teachers. The results delineate that the teachers enacted character education that covered cognitive, affective, and behavioural aspects. Nevertheless, these enactments were unplanned and unassessed. In the process of character selection, the teachers reflected on their contextual situations, past experiences, and future orientations. They encountered difficulties in character education due to the abundance of academic materials, and the lack of professional development programs and proactive involvement from other school members.